International Migration and Development: A Dyadic Analysis of the Americas, 1970–2010 - Sanderson, Matthew R.; Kentor, Jeffrey D. (Frontiers in Sociology, 2020)
This paper assesses the migration-development nexus from a new, relational perspective, providing a closer test of existing theories of cross-national dynamics, including migration and development. Using bilateral data, we assess the relationship between migration (im)balances and wage differentials between pairs of countries in the Americas, from 1970 to 2010. The analysis reveals a positive feedback between international migration and cross-national inequalities. Migration responds strongly to wage gaps, which motivate more uni-directional, or imbalanced migration flows in country-pairs. This relationship is particularly strong in contiguous countries. Similarly, wage gaps respond to migration imbalances, which increase per capita income differences in country-pairs, although the effect of migration on wage differentials is smaller than the effect of wage differentials on migration. Together, the results suggest that the migration-development nexus is characterized by a strong internal momentum.